2013
DOI: 10.1002/mnfr.201300345
|View full text |Cite
|
Sign up to set email alerts
|

The chemopreventive action of bromelain, from pineapple stem (Ananas comosusL.), on colon carcinogenesis is related to antiproliferative and proapoptotic effects

Abstract: Bromelain exerts antiproliferative and proapoptotic effects in colorectal carcinoma cells and chemopreventive actions in colon carcinogenesis in vivo. Bromelain-containing foods and/or bromelain itself may represent good candidates for colorectal cancer chemoprevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 37 publications
1
46
0
2
Order By: Relevance
“…Raw extracts obtained from mango (Kim et al ., ; Noratto et al ., ; Banerjee et al ., ), papaya (Gayosso‐García Sancho et al ., ; Nguyen et al ., ; Sancho et al ., ) and pineapple (Romano et al ., ; Gani et al ., ) pulps contain different phytochemicals with antiproliferative capacity, chemopreventive and citotoxic effects on different cancer cell lines with no apparent effects on normal cells (Yen et al ., ; Noratto et al ., ; Maisarah et al ., ). Several in vitro and in vivo studies have shown that ascorbic acid (Du et al ., ), polar phenolic compounds (Verma et al ., ; Gómez‐Caravaca et al ., ) and certain lipophilic compounds (Sancho et al ., ; Rascón‐Valenzuela et al ., ; Torres‐Moreno et al ., ) have a strong antiproliferative capacity on different cancer cell lines.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Raw extracts obtained from mango (Kim et al ., ; Noratto et al ., ; Banerjee et al ., ), papaya (Gayosso‐García Sancho et al ., ; Nguyen et al ., ; Sancho et al ., ) and pineapple (Romano et al ., ; Gani et al ., ) pulps contain different phytochemicals with antiproliferative capacity, chemopreventive and citotoxic effects on different cancer cell lines with no apparent effects on normal cells (Yen et al ., ; Noratto et al ., ; Maisarah et al ., ). Several in vitro and in vivo studies have shown that ascorbic acid (Du et al ., ), polar phenolic compounds (Verma et al ., ; Gómez‐Caravaca et al ., ) and certain lipophilic compounds (Sancho et al ., ; Rascón‐Valenzuela et al ., ; Torres‐Moreno et al ., ) have a strong antiproliferative capacity on different cancer cell lines.…”
Section: Resultsmentioning
confidence: 97%
“…are natural functional foods. They have a vast array of extractable phytochemicals with radical scavenging and antiproliferative capacity that, if eaten in sufficient amounts, may help to prevent breast, ovarian, colon, lung, leukaemia and prostate (García‐Solís et al ., ; Kim et al ., ; Noratto et al ., ; Nguyen et al ., ; Luo et al ., ; Romano et al ., ; Sancho et al ., ; Banerjee et al ., ; Gani et al ., ; Roleira et al ., ; Taing et al ., ) cancers. However, tropical fruits have usually a very short shelf life, which limits their distribution and commercialisation.…”
Section: Introductionmentioning
confidence: 98%
“…This distribution will be lost by increasing the inorganic amount (B_HA 20 and B_HA 30 ) probably due to the development of different intensities of interactions among ions. The charge density in the gelatin structure is fixed, demonstrating that the number of nucleation sites is uniformly distributed, and therefore the size/shape of nHA crystalline depend on the rate of crystalline growth, or rather [Ca 2+ ] [ PO43] concentration . Higher [Ca 2+ ] and [ PO43] values lead to the rate of crystalline growth accelerated.…”
Section: Discussionmentioning
confidence: 99%
“…Nipah contains a high concentration of minerals and vitamin A and has been used to treat several diseases, such as asthma, tuberculosis, and diabetic and liver diseases . Furthermore, with a high vitamin C content and antioxidant activity, pineapple has exhibited, among several promising properties, anti‐cancer and antihyperglycaemic effects …”
Section: Introductionmentioning
confidence: 99%